Economic intelligence as a way to achieve competitive advantage –Conceptual Approach- - Zerkout, Sara (Journal of Excellence for Economics and Management Research, 2020)
This study aimed to identify one of the most important keys to the success of business organizations in our time, achieving competitive advantages has become a guarantee to maintain the institution’s position in the market, and more than that, achieving leadership and excellence in an era characterized by change and continuous progress, and economic intelligence has been the way Effective to provide all that the institution needs about the competitive environment, the latter, which is characterized by instability and continuous development, which makes the institution between an environment of opportunities and threats, because it provided sufficient and comprehensive information that turned it into strengths for its benefit and made it discover its weaknesses in order to correct it in the future. This study has been addressed from the conceptual side through the use of the descriptive analytical approach by examining the most important concepts related to competitive advantage and economic intelligence and then analyzing the relationship between them and their implications on the business model of organizations in the long term.